Misunderstood, Overlooked, and Marginalized: The Construction of Jews and Antisemitism in EDI Policies and Plans in Canadian Higher Education - Marom, Lilach; Switzer, Ania (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
Equity, diversity, and inclusion (EDI) is a leading framework for addressing social justice issues in Canadian higher education. After October 7, 2023, occurrences of antisemitic incidents have surged on campuses in Canada. Yet, antisemitism is often not included or minimally mentioned in the existing EDI frameworks. The task of the EDI policies and plans is to ensure equity, diversity, and inclusion for all historically, persistently, or systematically marginalized groups. We examine the ways in which current EDI policies and plans include antisemitism and Jewish identity, analyzing EDI policies and plans collected from 28 universities across Canada. The content analysis reveals three patterns: (a) marginalization of antisemitism, (b) construction of Jewishness as a religious identity, and (c) coupling of antisemitism and Islamophobia. We argue that, at a time of growing divisiveness, politicization, and misinformation, universities who are committed to EDI should create a truly inclusive campus for people from diverse backgrounds and positions.